Development and characterization of micronutrient fortified sandwich biscuits with respect to nutritional composition and sensorial attributes to address malnutrition in school going children - Sana Sadaat; Muhammad Umair Arshad; Ali Imran; Muhammad Afzaal; Mohd Asif Shah (Cogent Food & Agriculture, 2023)
AbstractMicronutrient deficiencies have been escalating at an alarming rate in Pakistan that posed severe health discrepancies in population with special reference to children and women. The present study was designed to develop micronutrient enriched sandwich biscuits to address malnutrition in vulnerable segments. For the purpose, the study was comprised of three phases, i.e. development of micronutrient enriched sandwich biscuits in 1st phase, while in 2nd and 3rd phase, nutritional and sensorial characterization were done, respectively. After fortification in the flour and shortening, the mixture was supplemented with soyabean flour and various treatments followed by preparation of biscuits. A micronutrient premix containing zinc, iron, vitamins D, A, and folic acid as fortificants was added at 50% of RDA based on the percentage daily attributes of these nutrient contents in all formulations. Fortified sandwich biscuits were analyzed for proximate composition, mineral profile, antioxidants, and sensory characteristics. The data collected for each characteristic was statistically analyzed. Results revealed that biscuits produced from 100% white flour showed the highest moisture content, i.e. 8.30% and the lowest results (4.50%) were shown by T4, whereas, the highest values of crude ash, fat, fiber, protein, NFE calcium, magnesium, iron, iodine, vitamin A, vitamin E and Folic acid were exhibited by T4. As far as the antioxidant profile of micronutrient fortified biscuits was concerned, T4 showed the highest content of catechin (44.67 ± 0.24 mg/100 g) followed by carotenoids (34.11 ± 0.08 mg/100 g), rosmaneric acid (25.77 ± 0.23 mg/100 g), ascorbic acid (21.24 ± 0.02 mg/100 g), carnosol (20.6 ± 0.10 mg/100 g), propylgallate (14.02 ± 0.13 mg/100 g), genistein (8.30 ± 0.24 mg/100 g), rosmarinic (5.89 ± 0.03 mg/100 g) and daidzein (2.71 ± 0.15 mg/100 g). It was conclusively envisaged that the fortified sandwich biscuits exhibited the promising micronutrients composition with special reference to Vitamin A, E, iron and folic acid, additionally, it also holds array of antioxidants thus proved effectual to uplift the nutritional status of target population.